2016
DOI: 10.1161/jaha.115.003185
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging–Derived Renal Oxygenation and Perfusion During Continuous, Steady‐State Angiotensin‐II Infusion in Healthy Humans

Abstract: BackgroundThe role of kidney hypoxia is considered pivotal in the progression of chronic kidney disease. A widely used method to assess kidney oxygenation is blood oxygen level dependent (BOLD)–magnetic resonance imaging (MRI), but its interpretation remains problematic. The BOLD‐MRI signal is the result of kidney oxygen consumption (a proxy of glomerular filtration) and supply (ie, glomerular perfusion). Therefore, we hypothesized that with pharmacological modulation of kidney blood flow, renal oxygenation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 24 publications
2
29
1
Order By: Relevance
“…The maintenance ofQ O 2 during infusion of AngII is probably due to the maintenance of GFR (as reflected in increased FF), and thus the filtered load of sodium. Consistent with this proposition, van der Bel et al recently showed a strong association of reduced cortical oxygenation (as assessed by blood oxygen level-dependent magnetic resonance imaging) with increased filtration fraction during intravenous infusion of angiotensin II in man (van der Bel et al 2016). Differences between the systemic and renal effects of AngII and PE were greater in conscious than in anaesthetised animals.…”
Section: Figure 5 Responses To Intravenous Infusions Of Angiotensin-mentioning
confidence: 77%
See 1 more Smart Citation
“…The maintenance ofQ O 2 during infusion of AngII is probably due to the maintenance of GFR (as reflected in increased FF), and thus the filtered load of sodium. Consistent with this proposition, van der Bel et al recently showed a strong association of reduced cortical oxygenation (as assessed by blood oxygen level-dependent magnetic resonance imaging) with increased filtration fraction during intravenous infusion of angiotensin II in man (van der Bel et al 2016). Differences between the systemic and renal effects of AngII and PE were greater in conscious than in anaesthetised animals.…”
Section: Figure 5 Responses To Intravenous Infusions Of Angiotensin-mentioning
confidence: 77%
“…Consistent with this proposition, van der Bel et al recently showed a strong association of reduced cortical oxygenation (as assessed by blood oxygen level‐dependent magnetic resonance imaging) with increased filtration fraction during intravenous infusion of angiotensin II in man (van der Bel et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, another study demonstrated a dose-dependent decrease of renal blood flow accompanied by a minor decrease of oxygenation in the cortex, not in the medulla with continuous Ang II infusion in healthy humans (Bel et al, 2016). As discussed above, parenchymal hypoxia and fibrosis in the renal cortex of CKD patients using BOLD MRI and diffusion-weighted MRI has been shown (Inoue et al, 2011).…”
Section: Renal Oxygenation In Hypertension and Hypertensive Ckdmentioning
confidence: 99%
“…Early studies successfully validated the sensitivity of BOLD signals to diuretic-induced changes of renal oxygenation in healthy human subjects 3032 . Reduced renal blood flow in healthy subjects by continuous angiotensin-II infusion 33 correlated with the GFR/RPF to cortical R 2 * ratio. As GFR and RPF represent oxygen consumption and delivery respectively, their ratio should directly relate to how much oxygen is left, or tissue oxygenation.…”
Section: Non-contrast Mrimentioning
confidence: 92%